PENGARUH PENGETAHUAN DIGITAL MARKETING TERHADAP MINAT BERWIRAUSAHA MAHASISWA AKADEMI KESEJAHTERAAN SOSIAL AKK YOGYAKARTA - Mrs Istiqomah (Jurnal Socia Akademika, 2021)
The purpose of the research is to explore the influence of digital marketing knowledge on the entrepreneurial interests of students of AKK Yogyakarta Social Welfare Academy. Research method with descriptive quantitative research type, where the sample in the study as many as 80 respondents. Data collection techniques using research instruments using online questionnaires using google form. Independent research variables are digital marketing and dependent variables are entrepreneurial interests. Data analysis used is descriptive analysis and linear regression. The results of the study stated the influence of digital marketing knowledge on the entrepreneurial interests of students of the Akk Yogyakarta Academy of Social Welfare. The coefficient of determination is 0.5912 so that the data processing results show the value of the coefficient of determination of 0.349 or 34.9%. The calculation result means that digital marketing influenced entrepreneurial interest by 34.9% with the remaining 65% influenced by other factors not studied in this study.